Californian thistle and its variable response to the biological control agent Sclerotinia sclerotiorum - Smith, B.; Casonato, S.G.; Noble, A.; Bourd?t, G. (New Zealand Plant Protection, 2016)
Californian thistle (Cirsium arvense) is a problematic weed particularly in permanent pastures The fungus Sclerotinia sclerotiorum has potential as a bioherbicide to control this weed but its variable efficacy in historical field trials suggest that there are differences in susceptibility to S sclerotiorum within the species To test this hypothesis the responses of 32 New Zealand provenances of C arvense to a foliageapplied myceliumonbarley preparation of S sclerotiorum were compared under common conditions Significant differences between provenances were found supporting the hypothesis that there is variation within C arvense in New Zealand in its susceptibility to S sclerotiorum Further work will examine differences in the efficacy of fungal isolates against different C arvense provenances